Structural studies on yeast eIF5A using biomolecular NMR and molecular dynamics - Sigauke, Lester Takunda (Rhodes University, Faculty of Science, Department of Chemistry, 2015)
Eukaryotic initiation factor 5A, eIF5A, is a ubiquitous eukaryotic protein that has been shown to influence the translation initiation of a specific subset of mRNAs. It is the only protein known to undergo hypusination in a two-step post translational modification process involving deoxyhypusine synthase (DHS) and deoxyhypusine hydroxylase (DOHH) enzymes. Hypusination has been shown to influence translation of HIV-1 and HTLV-1 nuclear export signals, while the involvement of active hypusinated eIF5A in induction of IRES mediated processes that initiate pro-apoptotic process have inspired studies into the manipulation of eIF5A in anti-cancer and anti-diabetic therapies. eIF5A oligomerisation in eukaryotic systems has been shown to be influenced by hypusination and the mechanism of dimerisation is RNA dependent. Nuclear magnetic resonance spectroscopy approaches were proposed to solve the structure of the hypusinated eIF5A in solution in order to understand the influence of hypusination on the monomeric arrangement which enhances dimerisation and activates the protein. Cleavage of the 18 kDa protein monomer by introduction of thrombin cleavage site within the flexible domain was thought to give rise to 10 kDa fragments accessible to a 600 MHz NMR spectrometer. Heteronuclear single quantum correlation experiments of the mutated isotopically labelled protein expressed in E. coli showed that the eIF5A protein with a thrombin cleavage insert, eIF5AThr (eIF5A subscript Thr), was unfolded. In silico investigations of the behaviour of eIF5A and eIF5AThr (eIF5A subscript Thr) models in solution using molecular dynamics showed that the mutated model had different solution dynamics to the native model. Chemical shift predictors were used to extract atomic resolution data of solution dynamics and the introduction of rigidity in the flexible loop region of eIF5A affected solution behaviour consistent with lack of in vivo function of eIF5AThr (eIF5A subscript Thr) in yeast. Residual dipolar coupling and Tâ‚ relaxation times were calculated in anticipation of the extraction of experimental data from RDC and relaxation dispersion experiments based on HSQC measurable restraints.
Keywords: Molecular dynamics; Reverse transcriptase; HIV (Viruses); HIV infections; Eukaryotic cells; Yeast